Emulsions, suspensions, ointments, creams, pastes, suppositories and pessaries : laboratory practices - Tichý, Eduard; Šimunková, Veronika; Halenárová, Andrea (Comenius University in Bratislava, 2024)
Učebnica sa venuje rôznym farmaceutickým formám, pričom ponúka teoretické aj praktické informácie o príprave, vlastnostiach a použití týchto prípravkov. Publikácia je určená najmä študentom farmácie, farmaceutom a odborníkom v oblasti farmaceutickej vedy, ktorí chcú prehĺbiť svoje znalosti o rôznych typoch liečivých prípravkov. Kniha je rozdelená na kapitoly, ktoré sa zaoberajú jednotlivými formami liečiv: emulzie a suspenzie, masti a krémy, pasty, čapíky.----------- The textbook deals with various pharmaceutical forms, while offering both theoretical and practical information on the preparation, properties and use of preparations. The publication is intended mainly for pharmacy students, pharmacists and experts in the field of pharmaceutical science who want to deepen their knowledge of different types of medicinal preparations. The book is divided into chapters dealing with individual forms of medicines: emulsions and suspensions, ointments and creams, pastes, suppositories.